2014
DOI: 10.1136/bmjopen-2014-005689
|View full text |Cite
|
Sign up to set email alerts
|

A service-level action research intervention to improve identification and treatment of cannabis and related mental health issues in young Indigenous Australians: a study protocol

Abstract: IntroductionRegular cannabis use is associated with negative mental health impacts including psychosis, depression and anxiety. Rates of cannabis use have increased in Aboriginal and Torres Strait Islander communities in northern Australia within the last two decades, presenting a significant increased risk to young people's mental health in these regions. Improved screening, early detection and treatment for cannabis-related mental health issues are urgently required. This paper describes a service-level acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…They concluded that single‐measure strategies did not have sufficient evidence to be considered effective (although, in part, this was a result of the lack of evaluation). Bohanna et al 23 also proposed a preventative drug intervention protocol for Indigenous Australian youth. Prominent in their proposal was the need to collect baseline data to facilitate periodic evaluation of outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that single‐measure strategies did not have sufficient evidence to be considered effective (although, in part, this was a result of the lack of evaluation). Bohanna et al 23 also proposed a preventative drug intervention protocol for Indigenous Australian youth. Prominent in their proposal was the need to collect baseline data to facilitate periodic evaluation of outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Returning to the earlier discussion about the potential utility of the public health approach to program selection, it is clear from this study that this will inevitably rely on the availability of valid data about change − of the type that is simply not available. It is difficult to disagree with the arguments presented by both MacLean et al 24 and Bohanna et al 23 that it is only possible to establish program outcomes when valid and reliable tools are used to assess need, and that baseline data is required to document the extent to which change over time occurs. Even in contexts where randomised intervention trials are not feasible, there is clearly work to be done developing approaches to measurement that have utility in community settings.…”
Section: Discussionmentioning
confidence: 97%
“…Brief clinical intervention, cognitive behavioral therapies or raising awareness alone are unlikely to reduce cannabis demand and harms in a sustainable way in these populations in the short term. It is widely acknowledged in the face of mounting evidence that individual level interventions are insufficient to address substance misuse in Indigenous communities in Australia (Bohanna et al, 2014;Johnston et al, 2013;. We heard few suggestions that health clinics or schools should play a significant role, suggesting that participants considered these either inappropriate or inadequately resourced for cannabis demand reduction.…”
Section: Resources and Recommendationsmentioning
confidence: 99%
“…Participants receiving interventions or treatments tend to be defined by the service that will deliver the strategy e.g. "workplaces," "school," and "ante-natal clinic" (Bohanna et al, 2014;Graham, Campbell, West, & Clough, 2017). However, the evidence presented indicates that patterns in the use of and attitudes towards cannabis across the community are not drawn along these institutional lines.…”
Section: Resources and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation